HEALTH EDUCATION ON ACUTE RESPIRATORY SYNDROME AND URIC ACID TESTING FOR COMMUNITY IN GUNUNGSARI DISTRICT, PEMIJAHAN, BOGOR COUNTY - Febrial Hikmah; Rustiana Tasya Ariningpraja; Zahara Fadilla; Nicolaus Sri Widodo (Caring : Jurnal Pengabdian Masyarakat, 2021)
Efforts to prevent acute respiratory infections (ARI) are very important, because of the ease of transmission and can cause death. Health data from the Desa Gunung Sari Health Center, Kecamatan Pamijahan, Kabupaten Bogor in 2017 indicated that ARI was the most frequent complaint. The purpose of this community service is to educate health cadres about ARI. In addition, an examination of uric acid levels was held for the people of Desa Gunung Sari which was a series of counseling activities. The method used is counseling and direct examination. The counseling participants were 45 people and the uric acid examination was 146 people. The results showed that the cadres listened well to the counseling material, as seen in the correct answers to spontaneous questions during the counseling. The community's uric acid levels were mostly in the normal category and education helps increase public understanding of ARI. Thus, the continuity of similar activities is very much needed.